International change and the stability of multiethnic states : Yugoslavia, Lebanon, and crises of governance - Arfi, Badredine (Bloomington : Indiana University Press, 2005)
Develops a theory of governance for multiethnic states in crisis in the context of international change.
Introduction -- Debating state governance -- A theory of debating state governance -- Yugoslavia and the emerging Cold War, 1947-53 -- Yugoslavia and the waning Cold War, 1987-91 -- Lebanon, the Cold War penetration, and the rise of Nasserism, 1957-58 -- Lebanon and the metamorphosis of Arab-Israeli relations, 1973-75 -- Summary, alternative explanations, and implications.
Based on the author's thesis--Southern Illinois University at Carbondale.
Includes bibliographical references (pages 283-296) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: State, The; Ethnic conflict; Cultural pluralism; International organization; Security, International; World politics -- 1945-1989.; World politics -- 1989-; Yugoslavia -- Politics and government -- 1945-1980.; Yugoslavia -- Politics and government -- 1980-1992.; Lebanon -- Politics and government -- 1946-1975.; Cultural Diversity; État.; Conflits ethniques; Diversité culturelle; Organisation internationale; Sécurité internationale; Politique mondiale -- 1945-1989.; Politique mondiale -- 1989-; Yougoslavie -- Politique et gouvernement -- 1945-1980.; Yougoslavie -- Politique et gouvernement -- 1980-1992.; Liban -- Politique et gouvernement -- 1946-1975.; POLITICAL SCIENCE -- General; Cultural pluralism; Ethnic conflict; International organization; Politics and government; Security, International; State, The; World politics; Lebanon; Yugoslavia; Minderheitenfrage; Jugoslawien; Libanon; Since 1945